An MASW survey for landslide risk assessment: A case study in Valjevo, Serbia - Suto, K.; Urosevic, Milovan; Komatina, S. (Chang Mai University, 2016)
The MASW method is applied to the slope of landslide-risk area near Valjevo, Serbia. This is a part of SEG’s Geoscientists without Borders project, following the rain-caused disasters in the Balkan area in 2014. Association of Geoscientists and Environmentalists of Serbia organized the project involving specialists from around the world, local students, government individuals, and local communities. The data were primarily collected for reflection seismic analyses. The MASW processing used a subset of the data by extracting appropriate traces. The S-wave velocity sections analyzed through MASW are compared with the reflection seismic section and consistent features are identified to lead to a geologically plausible interpretation. This result will be integrated with electric resistivity survey and drilling data to contribute to designing disaster mitigation plan.